Coming home: veteran readjustment, postwar conformity and American film narratives, 1945-1948 - Brookes, Ian (2002)
The aftermath of World War II witnessed large-scale military demobilisation and. in its wake, a vast influx of returning servicemen. Their homecoming signalled a transition from military to civilian life which was often described as 'readjustment.' The term is usually taken to imply a process of homogenisation which engendered a condition of conformity in ex-servicemen and, by extension, in society at large. This thesis argues against this view and demonstrates that 'readjustment' wasn't intended to reproduce conformity but, on the contrary, was to provide the means for the reconversion of the 'conformist' ex-serviceman into the independent, autonomous citizen necessary for the functioning of a democratic society, especially in contradistinction to the conformism associated with the totalitarian Other. It was assumed that servicemen had become habituated to the military's authoritarian regimen of regulation and command which subsumed individuality. Hence, 'readjustment' was concerned with the 'nonconformist' individual who would become indispensable to a postwar' Americanism' which was being defensively constructed against totalitarianism and, moreover, against the 'totalitarian' implications of a conformism often seen as endemic in America as a mass society.